Islam Nusantara dan Pendidikan Agama: Studi Peran Pondok Pesantren dalam Pembentukan Karakter Generasi - Rizki Amanda Harahap; Mara Halim; Almadani Almadani; Fitria Sari Harahap; Alwi Murad Sofi Hasibuan (Reflection : Islamic Education Journal, 2025)
ThisThis research employs a quantitative method by analyzing data from 15 journals related to Islam Nusantara and religious education. The study aims to examine the role of Islamic boarding schools (pondok pesantren) as educational institutions based on Islam Nusantara in shaping the character of the younger generation. Pondok pesantren serves not only as a religious education institution but also as a center for preserving local cultural values that align with Islamic teachings. Through the Islam Nusantara approach, pesantren instill values of moderation, tolerance, and diversity in students, fostering noble character and adaptability in facing global challenges. Data were processed using descriptive statistics and correlation analysis to identify the relationship between pesantren education based on Islam Nusantara and the strengthening of students’ character. The findings reveal that pesantren education significantly contributes to the formation of a high-quality young generation. These findings affirm the relevance of Islam Nusantara in building a religious and culturally rooted generation.